The contribution of knowledge management in achieving and enhancing the competitive advantage: Apple as a case study - amina seddiki; ismahan guerza (Journal of Excellence for Economics and Management Research, 2022)
Knowledge is a significant strategic resource for organizations, therefore, interest in managing it and achieving its competitive advantages has increased. In this regard, our study focused on the knowledge management strategy of Apple as one of the most important pioneering companies in the technical and computer field. It was able to achieve competitive advantages and outperform its competitors; thus, answering the main research question which is: How does knowledge management contribute in achieving and enhancing competitive advantage in Apple company?The results of the study proved that the company used the strategy of knowledge management as a competitive advantage, by paying attention to the research and development process to provide distinguished services and products owing to a continuous creativity and innovation processes, which enabled it to enhance its market position and occupy the first ranks globally in the smart phone market; and achieve high profits, which contribute in enhancing its competitive advantage.